EXPLORING MOVIES AS EDUCATIONAL TOOL FOR JUNIOR HIGH SCHOOL STUDENTS - Armando, Eric Ginta; Aji, Gregorius Punto; Bram, Barli (Universitas Islam Nahdlatul Ulama Jepara, 2024)
This study investigated the efficacy of using movies as enrichment tools for enhancing vocabulary acquisition in seventh-grade students at SMP Kanisius Gayam Yogyakarta, Indonesia. Employing a quasi-experimental design with two classes, data from 30 students were gathered through pre-test and post-test vocabulary assessments, along with a perception-focused questionnaire. Results revealed a positive student perception of movies as effective enrichment tools. Statistical analyses, including difference tests and gain score calculations, demonstrated a significant enhancement in vocabulary knowledge for both groups. Notably, post-test scores showed no significant difference between the groups, indicating the approach's efficacy across diverse initial vocabulary levels. These findings prove that utilizing movies as enrichment tools can notably boost vocabulary acquisition in seventh-grade students, paving the way for innovative vocabulary learning methods in adolescent education.